Peningkatan Motivasi Belajar Mahasiswa Menggunakan Metode Hypnomotivation - Asmalinda, Wita; Sapada, Edy; Naue, Dian Adhe Bianggo (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2023)
Learning motivation is the driving or pulling force that causes a person's behavior towards a certain goal in order to have the will to act in learning. The hypnomotivation method is a learning method in conveying material, by exploring the subconscious, so that students become focused, relaxed and suggestive in accepting the subject matter provided. Alpha condition, it is possible to enter the material presented. The purpose of this activity is to increase student learning motivation during the Covid 19 pandemic using the hypnomotivation method. This community service activity uses training and mentoring methods with the main target being 42 first-level students of the Bachelor of Pharmacy study program. The training activities were carried out for 3 days, consisting of preparation, implementation and evaluation activities. It was concluded that training and mentoring using the hypnomotivation method ran smoothly and successfully and was able to increase student learning motivation.